Antimicrobial Activity of Gotu Kola (Centella asiatica) Leaf Extract as an Alternative to Herbal Beverage - Nadya Treesna Wulansari; A.A.Istri Mas Padmiswari; Kadek Buja Harditya (Jurnal Biologi Tropis, 2023)
Pathogenic microorganisms include Aspergillus sp., Escherichia coli and Staphylococcus aureus. Antibiotic administration during the treatment of contagious illnesses may cause bacterial resistance. Treatment with herbal medicine, made from natural ingredients, is an option to prepare for this. A plant known as gotu kola (Centella asiatica) has the capacity to become a herbal beverage. The intention of this research was to discover whether gotu kola leaves, a herbal beverage, had any antimicrobial properties. This study was categorized as an experimental study with an entirely random approach. This study performing an analysis of variance on the data, the Duncan's Multiple Range Test was conducted. The findings demonstrated that Staphylococcus aureus and Escherichia coli bacteria could not grow when exposed to gotu kola leaf extract. Gotu kola leaf preparation has the ability to stop Staphylococcus aureus and Escherichia coli from growing. The greatest average hindrance of 9.67 ± 0.36 mm and 10.12 ± 1.12 mm against Escherichia coli and Staphylococcus aureus bacteria was obtained by 100% concentrated infusion from the leaves of gotu kola. Alkaloids, flavonoids, and tannins are examples of the gotu kola leaf extract's metabolite components that can increase the inhibitory power of the herb. However, the Aspergillus sp. in this research was not inhibited by the gotu kola extract. The body structure of the Aspergillus sp. and length of storing of the gotu kola extract are probable causes for there was not inhibitory effect.